An open study on the efficacy of a recombinant Der f 2 (Dermatophagoides farinae) immunotherapy in atopic dogs in Hungary and Switzerland. Issue 4 (17th June 2018) - Fischer, Nina; Tarpataki, Noémi; Leidi, Federica; Rostaher, Ana; Favrot, Claude
Abstract : Background: Previously published studies evaluating a recombinant Der f 2‐based immunotherapy have demonstrated efficacy in the treatment of dogs experimentally and naturally sensitized to house dust mites (HDM). Der f 2 sensitization is thought to play a minor role in European atopic dogs sensitized to HDM. Objective: The study evaluated the short‐term efficacy of a recombinant Der f 2 product in the treatment of naturally sensitized atopic dogs in Switzerland and Hungary. Animals: Fifteen atopic dogs with positive test reactions to Dermatophagoides farinae (Df). Material and Methods: Recombinant Der f 2 allergens were injected subcutaneously at increasing doses once weekly for 6 weeks. Canine Atopic Dermatitis Extent and Severity Index (CADESI‐04), pruritus Visual Analog Scale (pVAS) and medication scores were assessed at days 0 and 42. Efficacy was recorded as excellent, good, fair or poor, depending on the number of scores decreasing by more than 50%. Results: Mean CADESI, pVAS and medication scores at inclusion were 35, 6 and 15 (SD = 30, 2, 7), respectively. At Day 42 the scores decreased to 8, 3 and 5, respectively (Wilcoxon matched pairs signed rank tests P = 0.0002, 0.002 and 0.001). Four dogs were classified as excellent responders with a reduction of >50% in all three scores. Nine dogs were classified as good (five) or fair (four) responders and scores deteriorated in two dogs. Conclusion: These data suggest that recombinant Der f2 allergens may be as effective and show benefit faster than traditional allergen immunotherapy in European dogs sensitized to Df. Abstract : Background – Previously published studies evaluating a recombinant Der f 2‐based immunotherapy have demonstrated efficacy in the treatment of dogs experimentally and naturally sensitized to house dust mites (HDM). Der f 2 sensitization is thought to play a minor role in European atopic dogs sensitized to HDM.Objective – The study evaluated the short‐term efficacy of a recombinant Der f 2 product in the treatment of naturally sensitized atopic dogs in Switzerland and Hungary.Conclusion – These data suggest that recombinant Der f 2 allergens may be as effective and show benefit faster than traditional allergen immunotherapy in European dogs sensitized to Df.